Application of Lakshmikantham's monotone-iterative technique to the solution of the initial value problem for impulsive integro-differential equations. (1993) - Bainov Bainov, D. D. D. D.; Hristova Hristova, S. G. S. G.
Abstract : In the present paper, a technique of V. Lakshmikantham is applied to approximate finding of extremal quasisolutions of an initial value problem for a system of impulsive integro-differential equations of Volterra type.